A preparation method of polybutadiene latex and transparent ABS resin

By using a second monomer containing a methyl/cyclic structure in the polybutadiene latex to regulate the molecular chain movement of the dispersed phase, the problem of inconsistent refractive index changes during temperature fluctuations is solved, and the problem of inconsistent refractive index changes in the transparent ABS resin is achieved. Better optical properties over a wide temperature range.

CN116162204BActive Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310187141.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-02
Publication Date
2025-02-18
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

When the temperature fluctuates in use, the two phases have inconsistent changes in the refractive index, resulting in a decrease in the transparency effect and showing a higher haze value.

Method used

By introducing a second monomer containing a methyl/cyclic structure into the polybutadiene latex, the molecular chain movement of the dispersed phase is regulated, and the change trend of the refractive index fluctuates with temperature, so that it is wider with the continuous phase refractive index. Maintain better matching within the temperature range.

Benefits of technology

It achieves better optical properties of transparent ABS resin in a wider usage temperature window, reducing the impact of temperature fluctuations on the transparent effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004104227370000021
    Figure BDA0004104227370000021
  • Figure BDA0004104227370000031
    Figure BDA0004104227370000031
  • Figure FDA0005133901010000011
    Figure FDA0005133901010000011
Patent Text Reader

Abstract

The invention discloses a method for preparing a polybutadiene latex for transparent ABS. In the process of preparing a small-particle polybutadiene latex, the invention adopts a second monomer having a methyl / cyclic structure. When the latex prepared by the method is used to further prepare a transparent ABS resin, since the methyl / cyclic structure has a greater motion steric hindrance, when the transparent ABS is used at a fluctuating temperature, the refractive index matching of the two phases is better, and the prepared transparent ABS exhibits better optical properties in a wider use temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method for preparing polybutadiene latex, and belongs to the field of ABS resin materials. Background Art

[0002] ABS resin is a two-phase polymer, which is obtained by bulk polymerization / emulsion graft polymerization. The polybutadiene latex particles uniformly dispersed in the continuous phase SAN are used to toughen the matrix SAN. As it has the characteristics of three monomer polymers of butadiene / styrene / acrylonitrile, it has excellent comprehensive performance among general plastics.

[0003] Because it is a two-phase polymer, the dispersed phase polybutadiene latex particles and the continuous phase SAN have inconsistent refractive indices (polybutadiene latex is 1.515, SAN is 1.573), the finished ABS resin is usually opaque and cannot be used in the application field of transparent parts.

[0004] At present, there are two ways to achieve the transparency of finished ABS:

[0005] 1) Adjusting the particle size of polybutadiene latex. By reducing the particle size, the refraction / scattering of visible light at the interface between the two phases is reduced, thereby achieving transparency;

[0006] 2) Use copolymerization to increase the refractive index of the dispersed phase or reduce the continuous phase, so that the refractive index of the two phases matches, eliminates refraction / scattering on the interface between the two phases, and achieves transparency;

[0007] Method 1) is usually not used alone because the impact performance of the product decreases significantly after the particle size is reduced. Method 2) is the most common transparent ABS production method at this stage. For example, patent CN101336255 uses MMA / styrene / acrylonitrile copolymerization to reduce the refractive index of the continuous phase to within 0.002 of the dispersed phase, thereby realizing the preparation of transparent ABS.

[0008] Patent CN104136530 uses copolymerization of acrylic acid ester monomers to adjust the refractive index difference among dispersed phase polybutadiene latex, polybutadiene latex graft, and continuous phase SAN to <0.005, thereby achieving the preparation of transparent ABS.

[0009] Patent CN106221114 / CN114736334 uses the method of introducing styrene copolymerization into the dispersed phase and introducing acrylic ester monomer copolymerization into the continuous phase to control the difference in refractive index between the two phases, thereby achieving resin transparency.

[0010] The above methods can all achieve the preparation of transparent ABS, but they all ignore a key technical problem: the refractive index of the two phases of the prepared transparent ABS is not constant in actual application. Studies have found that when the transparent ABS has a large fluctuation in use temperature, the refractive index changes with the temperature, and the refractive index change rate of the two phases is significantly different. At higher / lower use temperatures, the transparency of the transparent ABS is significantly reduced, showing a higher haze value.

[0011] Therefore, it is necessary to find a method to control the difference in the refractive index of the two phases while making the temperature influence trend of the refractive index of the two phases consistent, so as to achieve a wider temperature use window for the finished transparent ABS. Summary of the invention

[0012] The object of the present invention is to provide a method for preparing a polybutadiene latex. The prepared latex can be further used to prepare a transparent ABS resin. The finished transparent ABS has better optical properties within a wider use temperature window.

[0013] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0014] A method for preparing a transparent polybutadiene latex for ABS, comprising:

[0015] Deionized water, an emulsifier, butadiene, a second monomer, an electrolyte, a chain transfer agent, and an initiator are added into a reactor to carry out an emulsion polymerization reaction, and when the conversion rate reaches more than 98% (e.g., 98-99%), unreacted butadiene is removed to obtain a polybutadiene latex with a small particle size of 95-105 nm;

[0016] The mass dosage of each component is as follows:

[0017]

[0018]

[0019] The emulsifier described in the present invention is selected from one or more of potassium salt or sodium salt of disproportionated rosin acid, oleic acid, linoleic acid, stearic acid and dodecylbenzene sulfonic acid; the electrolyte is selected from one or more of sodium carbonate, potassium carbonate, sodium chloride, potassium phosphate and sodium sulfite; the chain transfer agent is selected from one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan and n-octadecyl mercaptan; the initiator can be one or more of sodium persulfate, potassium persulfate, cumene hydroperoxide and tert-butyl hydroperoxide.

[0020] The second monomer of the present invention is one of 3-methyl-1,3-pentadiene, 3-methyl-1,2-pentadiene, 2,3-dimethyl-1,3-butadiene, 1,4-cyclohexadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene, 1,5-cyclooctadiene, bicyclo[2.2.1]heptadiene-2,5-diene, and spiro[2.4]heptadiene-4,6-diene.

[0021] The polymerization reaction temperature of the present invention is 60°C-70°C, preferably 60°C-65°C;

[0022] The method for removing unreacted butadiene described in the present invention can be achieved by flash evaporation, steam stripping and the like.

[0023] The small-particle polybutadiene latex prepared by the method of the present invention can be further agglomerated to increase the particle size to an optimal value, and then used to prepare transparent ABS resin.

[0024] The invention also relates to a transparent ABS resin, which is prepared by using the polybutadiene latex.

[0025] The beneficial effects of the present invention are as follows: the prepared polybutadiene latex adopts a second monomer containing a methyl / cyclic structure. Studies have shown that when the dispersed phase has the above structure, the movement of the dispersed phase molecular chain is hindered as the use temperature fluctuates, the trend of its refractive index changing with temperature fluctuations is significantly slowed down, and it has better matching with the continuous phase refractive index in a wider temperature range, and the finished resin has better optical properties in a wider use temperature window. DETAILED DESCRIPTION

[0026] The present invention is further described below by means of several examples and comparative examples, which are however not intended to limit the scope of protection of the present invention.

[0027] Test method:

[0028] Latex particle size: 1 g of latex was mixed with 100 g of deionized water, and the average particle size was measured using a Malvern Mastersizer laser particle size analyzer according to the dynamic laser scattering method;

[0029] Gel content: The rubber polymer was coagulated with dilute acid, washed with deionized water, dried in a vacuum oven at 60°C for 24 hours, and the resulting gel blocks were cut into pieces with scissors. 1 g of the gel block fragments were immersed in 100 g of toluene and stored at room temperature for 48 hours. The resulting solution was separated into sol and gel (insoluble matter). The separated gel part was dried in an oven at 85°C for 6 hours, the weight of the dried gel was tested, and the gel content was calculated using the following formula;

[0030] Gel content = gel weight after drying / sample weight * 100%

[0031] The prepared latex performance needs to be agglomerated with acetic acid to form a 300nm latex, and then grafted with MMA, acrylonitrile and styrene to make a grafted powder, and mixed with MSAN with a refractive index of 1.515 in a fixed ratio to obtain a transparent ABS resin for performance testing. The preparation process is as follows:

[0032] Agglomeration of small particle size latex: 100 parts of the prepared emulsion of the present invention were added with 20 parts of 5% acetic acid aqueous solution, slowly stirred at room temperature and pressure, and after reacting for 2 hours, 5% KOH aqueous solution was added to adjust the pH value of the reaction solution to about 11, to obtain an agglomerated latex emulsion with a particle size of 290-310 nm;

[0033] Agglomerated latex grafting: 100 parts of the latex emulsion obtained by agglomeration were taken, 0.001 parts of FeSO4 were added thereto, and the mixture was stirred evenly. After the reaction system was gradually heated to 70°C, 0.1 parts of cumene hydroperoxide, 12.2 parts of MMA, 3.1 parts of styrene, 1 part of acrylonitrile, 0.2 parts of tert-dodecyl mercaptan, 0.3 parts of potassium oleate and 10 parts of deionized water were gradually added thereto. The continuous feeding time was 3 hours. After the feeding was completed, the reaction was continued for 3 hours to obtain a grafted latex emulsion with a grafting rate of about 40%;

[0034] Coagulation / drying: 100 parts of the grafted latex emulsion obtained above were added to a reaction kettle, heated to 95°C, 1.2 parts of H2SO4 and 40 parts of deionized water were gradually added thereto, the temperature was maintained, and the reaction was uniformly stirred for 1 hour. The obtained coagulated emulsion was filtered with a 200-mesh stainless steel filter cloth to obtain a wet grafted powder, which was dried in a vacuum drum dryer at 60°C and 2KPaA for 4 hours to obtain a grafted powder with a moisture content of <1%;

[0035] Blending: Using a twin-screw extruder at 200-220° C., take LG XT500 as the blending MSAN phase, and blend according to the blending ratio of XT500: the above-mentioned grafted powder = 75 / 25. After cooling and granulation, transparent ABS finished resin slices are obtained.

[0036] Impact performance test: The ABS resin slices obtained by blending are used to prepare samples and perform impact performance tests according to the GB / T1043 hard plastic simply supported beam impact test method;

[0037] Transmittance / haze: The transmittance / haze index of the resin at -23℃ / 25℃ / 60℃ is measured according to ASTM D1003.

[0038] Example 1

[0039] 0.9 g of potassium oleate, 1.1 g of potassium disproportionate rosin acid, 95 g of butadiene, 5 g of 2,3-dimethyl-1,3-butadiene, 0.6 g of potassium carbonate, 0.7 g of tert-dodecyl mercaptan (TDM) and 250 g of deionized water were added into a reactor, heated to 65° C., 0.25 g of potassium persulfate was added to initiate emulsion polymerization, and after 12 hours of reaction, the butadiene conversion rate in the reactor was 98.5%. The reaction was stopped, and unreacted butadiene was removed by vacuum flash evaporation to obtain a small-particle polybutadiene latex emulsion with a latex particle size of 97 nm.

[0040] The gel content of the polybutadiene latex was 77% as measured by the aforementioned analytical method. The latex was further prepared into agglomerated latex emulsion, grafted latex emulsion, grafted powder and transparent ABS resin in sequence by the aforementioned method.

[0041] The impact strength of the prepared transparent ABS resin tested by the above analysis method is 17.4 J / m. The transmittance / haze indexes of the transparent ABS resin at -23°C / 25°C / 60°C are (-23°C / 89.2% / 4.1), (25°C / 90.1% / 2.1), and (60°C / 88.9% / 3.4) respectively.

[0042] Example 2

[0043] 0.7 g of potassium oleate, 1.2 g of potassium disproportionate rosin acid, 92 g of butadiene, 8 g of bicyclo[2.2.1]hept-2,5-diene, 0.4 g of potassium carbonate, 0.5 g of tert-dodecyl mercaptan and 200 g of deionized water were added to a reactor, heated to 62° C., 0.3 g of potassium persulfate was added to initiate emulsion polymerization, and after 13 hours of reaction, the butadiene conversion rate in the reactor was 98.7%. The reaction was stopped, and unreacted butadiene was removed by vacuum flash evaporation to obtain a small-particle polybutadiene latex emulsion with a latex particle size of 102 nm.

[0044] The gel content of the polybutadiene latex was 72% as measured by the aforementioned analytical method. The latex was further prepared into agglomerated latex emulsion, grafted latex emulsion, grafted powder and transparent ABS resin in sequence by the aforementioned method.

[0045] The impact strength of the prepared transparent ABS resin tested by the above analysis method is 16.7 J / m. The transmittance / haze indexes of the transparent ABS resin at -23°C / 25°C / 60°C are (-23°C / 90.2% / 4.3), (25°C / 91.3% / 1.7), and (60°C / 89.9% / 3.8) respectively.

[0046] Example 3

[0047] 1 g of potassium oleate, 1.2 g of potassium disproportionate rosin acid, 97 g of butadiene, 3 g of spiro[2.4]hept-4,6-diene, 0.7 g of potassium carbonate, 0.3 g of tert-dodecyl mercaptan and 300 g of deionized water were added into a reactor, heated to 67°C, 0.32 g of potassium persulfate was added to initiate emulsion polymerization, and after 11 hours of reaction, the butadiene conversion rate in the reactor was 99.1%, the reaction was stopped, and unreacted butadiene was removed by vacuum flash evaporation to obtain a small-particle polybutadiene latex emulsion with a latex particle size of 95 nm.

[0048] The gel content of the polybutadiene latex was 82% as measured by the above analytical method. The above latex was further prepared into agglomerated latex emulsion, grafted latex emulsion, grafted powder and transparent ABS resin in sequence by the above method.

[0049] The impact strength of the prepared transparent ABS resin tested by the above analysis method is 16.9 J / m. The transmittance / haze indexes of the transparent ABS resin at -23°C / 25°C / 60°C are (-23°C / 89.7% / 3.5), (25°C / 90.5% / 2.4), and (60°C / 89.3% / 4.2), respectively.

[0050] Example 4

[0051] 0.5 g of potassium oleate, 1.7 g of potassium disproportionate rosin acid, 95 g of butadiene, 5 g of 1,3-cycloheptadiene, 0.3 g of potassium carbonate, 0.5 g of tert-dodecyl mercaptan and 250 g of deionized water were added into a reactor, heated to 65°C, 0.25 g of potassium persulfate was added to initiate emulsion polymerization, and after 13 hours of reaction, the butadiene conversion rate in the reactor was 98.2%. The reaction was stopped and unreacted butadiene was removed by vacuum flash evaporation to obtain a small-particle polybutadiene latex emulsion with a latex particle size of 103 nm.

[0052] The gel content of the polybutadiene latex was 79% as measured by the aforementioned analytical method. The latex was further prepared into agglomerated latex emulsion, grafted latex emulsion, grafted powder and transparent ABS resin in sequence by the aforementioned method.

[0053] The impact strength of the prepared transparent ABS resin tested by the above analysis method is 17.3 J / m. The transmittance / haze indexes of the transparent ABS resin at -23°C / 25°C / 60°C are (-23°C / 89.5% / 3.6), (25°C / 90.3% / 1.8), and (60°C / 88.8% / 3.7), respectively.

[0054] Comparative Example 1

[0055] 0.9 g of potassium oleate, 1.1 g of potassium disproportionate rosin acid, 100 g of butadiene, 0.6 g of potassium carbonate, 0.7 g of tert-dodecyl mercaptan and 250 g of deionized water were added into a reactor, heated to 65° C., 0.25 g of potassium persulfate was added to initiate the polymerization reaction. After 12 hours of reaction, the butadiene conversion rate in the reactor was 98.9%. The reaction was stopped and unreacted butadiene was removed by vacuum flash evaporation to obtain a polybutadiene latex emulsion with a particle size of 98.5 nm.

[0056] The gel content of the polybutadiene latex was 81% as measured by the above analytical method. The above latex was further prepared into agglomerated latex emulsion, grafted latex emulsion, grafted powder and transparent ABS resin in sequence by the above method.

[0057] The impact strength of the prepared transparent ABS resin tested by the above analysis method is 17.2 J / m. The transmittance / haze indexes of the transparent ABS resin at -23°C / 25°C / 60°C are (-23°C / 88.2% / 7.3), (25°C / 89.9% / 2.3), and (60°C / 87.8% / 6.4), respectively.

Claims

1. A method for preparing a polybutadiene latex, comprising: Deionized water, an emulsifier, butadiene, a second monomer, an electrolyte, a chain transfer agent, and an initiator are added into a reactor to carry out an emulsion polymerization reaction. When the butadiene conversion rate reaches a certain value, unreacted butadiene is removed to obtain a small-particle polybutadiene latex. The second monomer is at least one of 3-methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 1,4-cyclohexadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene, 1,5-cyclooctadiene, bicyclo[2.2.1]heptadiene-2,5-diene, and spiro[2.4]heptadiene-4,6-diene.

2. The method according to claim 1, characterized in that: The certain value is 98% or more.

3. The method according to claim 1, characterized in that: The certain value is 98%-99%.

4. The method according to claim 1, characterized in that: The small particle size is 95-105 nm.

5. The method according to claim 1, characterized in that: The mass dosage of each component is as follows:

6. The method according to claim 1, characterized in that: The mass dosage of each component is as follows:

7. The method according to any one of claims 1 to 6, characterized in that: The emulsifier is selected from one or more of disproportionated rosin acid, oleic acid, linoleic acid, stearic acid and potassium salt or sodium salt of dodecylbenzene sulfonic acid.

8. The method according to any one of claims 1 to 6, characterized in that: The electrolyte is selected from one or more of sodium carbonate, potassium carbonate, sodium chloride, potassium phosphate and sodium sulfite.

9. The method according to any one of claims 1 to 6, characterized in that: The chain transfer agent is selected from one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan and n-octadecyl mercaptan.

10. The method according to any one of claims 1 to 6, characterized in that: The initiator is selected from one or more of sodium persulfate, potassium persulfate, cumene hydroperoxide, and tert-butyl hydroperoxide.

11. The method according to any one of claims 1 to 6, characterized in that: The polymerization reaction temperature is 60°C-70°C.

12. The method according to claim 11, characterized in that: The polymerization reaction temperature is 60°C-65°C.

13. The method according to claim 1, characterized in that: The method for removing unreacted butadiene includes flash distillation and stripping.

14. A transparent ABS resin prepared by using the polybutadiene latex prepared by the method according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Preparation method of small-particle-size high-crosslinking polybutadiene and copolymer latex thereof

    CN111848869A